beta-Naphthoflavone and 3'-methoxy-4'-nitroflavone exert ambiguous effects on Ah receptor-dependent cell proliferation and gene expression in rat liver 'stem-like' cells - Zatloukalová, Jirina; Svihálková-Sindlerová, Lenka; Kozubík, Alois; Krcmár, Pavel; Machala, Miroslav; Vondrácek, Jan (Biochemical pharmacology, 2007)
Both natural and synthetic flavonoids are known to interact with the aryl hydrocarbon receptor (AhR); however, their agonist/antagonist properties in vitro have been so far studied mostly in the context of cytochrome P450 1A1 gene (Cyp1a1) regulation. We investigated effects of two synthetic flavones known either as AhR agonist (beta-naphthoflavone; BNF) or antagonist (3'-methoxy-4'-nitroflavone; 3M4NF), using an in vitro model of liver 'stem-like' cells, on expression of various AhR target genes and AhR-dependent cell proliferation. We found that the presumed antagonist 3M4NF induces a partial nuclear translocation and activation of AhR. Although inhibiting the 2,3,7,8-tetrachlorodibenzo-p-dioxin-induced Cyp1a1 expression, 3M4NF alone induced a minor increase of CYP1A1 mRNA and protein. However, 3M4NF did not induce AhR binding to synthetic dioxin response elements (DRE). In contrast to Cyp1a1, 3M4NF induced a marked expression of other AhR-regulated genes, such as Cyp1b1 and Nqo1, as well as transcriptional repression of Cdh13 gene, confirming that its effects may be promoter-context specific. Like BNF, 3M4NF induced AhR-dependent cell proliferation of contact-inhibited rat liver 'stem-like' WB-F344 cells, associated with a marked upregulation of Cyclin A, as well as the downregulation of proteins involved in formation of cell-cell contacts. Based on these experimental findings, we conclude that partial agonists/antagonists of AhR can increase cell proliferation rate and AhR-dependent genes expression in both cell type- and gene-specific manner. The specificity of effects of flavones on diverse AhR targets should be taken into account, when studying AhR signaling using presumed AhR antagonists.
Keywords: hepatocyty; Liver; flavonoidy; Animals; proliferace buněk; játra; Flavonoids; Rats, Inbred F344; receptory aromatických uhlovodíků; NAD(P)H Dehydrogenase (Quinone); Cytochrome P-450 CYP1A1; kultivované buňky; NAD(P)H dehydrogenasa (chinon); Hepatocytes; Cells, Cultured; Receptors, Aryl Hydrocarbon; cytochrom P-450 CYP1A1; beta-naftoflavon; potkani inbrední F344; Cell Proliferation; krysa rodu Rattus; exprese genu; Cadherins; zvířata; beta-Naphthoflavone; kadheriny; Rats; Gene Expression